AEROBIC, ANAEROBIC AND HAEMATOLOGIC RESPONSES OF COLLEGE OF EDUCATION MALE STUDENTS TO DEHYDRATION REHYDRATION AND SUPERHYDRATION (1992)
The purpose of the study was to investigate the influence of dehydration, rehydration and superhydration on the aerobic, anaerobic, haematologic and some related body composition variables in College of Education male students. A repeated measures experimental design was used for the study. The subjects were twenty healthy Physical and Health Education students of Ondo State College of Education, Ikere- Ekiti. They were volunteers certified fit by the physician .before they were allowed to take part in the study. The variables tested were maximum oxygen consumption (Maxvo 2). Recovery heart rate, myocardial oxygen consumption, speed, power, packed cell volume (PVC), osmotic fragility, percent body fat and lean body weight. The subjects were pre-assessed on the selected variables. For the first condition, the subjects were dehydrated so that over 3% of the body weight of each was lost before the exercise and subsequent reassessment. Also, they were allowed two weeks after dehydration for rehydration to take place before being exposed to exercise and evaluation. For superhydration, the subjects drank 2 litres of water each 30 minutes before the evaluation took place. Nine sub-hypotheses were formulated and tested at significant level of 0.05. The data were analysed, using descriptive and inferential statistics. The descriptive statistics used were mean, range and standard deviation. The inferential statistics was the ANOVA. The method of Scheffe was used to determine where the differences. The results showed significant differences in weight, speed, recovery heart rate, maximum oxygen consumption (Maxvo 2), myocardial oxygen consumption as well as the haematologic variables of packed cell volume (PVC) and Osmotic fragility among the three levels of hydration. Superhydration affected only maximum oxygen consumption (Maxvo2). Recovery heart rate, myocardial oxygen consumption, PCV and Osmotic fragility. Other variables were not influenced significantly by the various conditions. Its concluded that dehydration was detrimental to physical performances and red blood cells while superhydration enchanced aerobic capacity.